A laboratory-developed TaqMan Array Card for simultaneous detection and genotyping of Group A rotavirus - Araujo, Irene T. (2015)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Rio de Janeiro, RJ, Brasil.